Gender Segregation in Childhood Friendships and the Gender-Equality Paradox - Manuel Bagues; Natalia Zinovyeva (Institute of Labor Economics (IZA), 2025)
Gender segregation in higher education persists across developed countries and is paradoxically stronger in wealthier, more gender-equal societies. Using data from over 500,000 children across 37 Western countries, we show that this segregation has roots in childhood. We document a strong correlation at the country level between segregation in higher education and in childhood friendships. Longitudinal data from 10,000 British households further shows that children with fewer opposite-sex friends at age 7 are significantly more likely to select gender-dominated educational subjects a decade later. The stronger segregation observed in richer countries seems to reflect economic prosperity rather than backlash against gender equality: while children from wealthier households report fewer cross-gender friendships, those whose parents hold more gender-egalitarian views have more opposite-sex friends. We identify two mechanisms explaining this income gradient: affluent families' structured activities that emphasize children's self-expression foster gender-segregated environments, and higher-income children's personality traits reduce demand for cross-gender friendships.
Keywords: J16; I21; Z13; 330; gender equality paradox; cross-gender friendships; women in STEM